Climate change problem: new challenges of international legal regulation - Aliyev, Amir Ibrahim-oglu; Huseynov, Turgay Imamgulu-oglu (Journal of the Belarusian State University. Law, 2020)
The article is devoted to the analysis of the problems of climate change in the light of the changes taking place in the world, in particular, against the backdrop of COVID-19. The problems associated with climate change are identified and the importance of their international legal regulation is noted. The need to improve the international legal climate regime is considered in the light of the existing challenges. The importance of providing a more systematic approach to finding an acceptable balance between the interests of different groups of participating states using effective forms and methods of cooperation, as well as stimulating innovative solutions, is noted. Along with traditional challenges, the authors identify problems caused by the spread of COVID-19 and adversely affecting the state of the environment, in particular climate change. The initiatives related to the fight against climate change are identified that will contribute to the post-crisis recovery and updating the issue of their international legal regulation.